Pengembangan Unit Produksi Sebagai Sarana Wirausaha Pertanian Bagi Siswa SMKN PP Merangin - Edi Susanto; Rita Rahmatillah; Nela Silvia; Sarinah Sarinah (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2026)
One of the major challenges in vocational education today is not merely producing technically skilled graduates, but also nurturing students who are capable of creating their own employment opportunities, particularly in the agricultural sector facing market dynamics and limited formal job absorption. School production units offer strategic potential as contextual learning platforms that integrate real work practices with entrepreneurial value formation. This study explores the development of production units as a medium for agricultural entrepreneurship learning at SMKN PP Merangin. A descriptive qualitative case study was conducted involving vocational teachers and agricultural students. Data were collected through semi-structured interviews, observations, and document analysis, and analyzed thematically. The findings indicate that production units provide authentic learning experiences that enhance practical skills and foster responsibility, discipline, and independence among students. However, the integration of entrepreneurial objectives into instructional planning remains limited. The study concludes that strengthening curriculum integration, teacher facilitation, and school management support is essential to optimize production units as an effective medium for agricultural entrepreneurship learning.